PERSEPSI DAN EKSPEKTASI DOKTER TERHADAP JASA MEDISDI RS PKU MUHAMMADIYAHNANGGULAN - Heru Yuliyanto; Erwin Santosa (Universitas Muhammadiyah Yogyakarta, 2015)
Background: General practitioners / specialist considerations a hospital which are most suitable to be used as a practice. There are several considerations in determining a doctor's office, one of which is the most powerful pull factor is the amount of medical services to be received from the PKU Muhammadiyah Hospital Nanggulan. Objectives: in this study is to describe the perceptions and expectations of general practitioners and specialists for medical services in PKU Muhammadiyah Hospital Nanggulan. Method: This study used a qualitative research approach. The study was conducted in PKU Muhammadiyah Hospital Nanggulan, KulonProgo, Yogyakarta during the month of July 2011 - February 2015. The subjects in this study were four general practitioners and four specialists in PKU Muhammadiyah Hospital Nanggulan who has had a license to practice. Data analyze used descriptive qualitatively. Result: Perception of general practitioners / specialists in PKU Muhammadiyah Hospital Nanggulan vary according to the characteristics of informants that includes needs, age, status, workplace, social conditions, and hope the doctor. General practitioners revealed that remuneration has been timely received, but not yet in accordance with the load of work done. Specialist physicians perceive that the medical services received are in accordance with the assumption that the meaning of work for informants as worship and religious symbols. General practitioners hope that hospitals provide child support and medical benefits. Specialist doctors have hope in order to meet current needs and hope that PKU Muhammadiyah Hospital Nanggulan can improve the quality and infrastructure for specialists, provide health insurance for specialists, and in order to improve reply to specialist medical services in accordance with the development of the hospital. Conclusion: Remuneration received by general practitioners has on time, but not in accordance with the load of work done. Medical services received by specialists are in accordance with the assumption that the meaning of work for informants as worship and religious symbols.